Comparative evaluation of liver function test in refractive psoriasis patients treated with tofacitinib and apremilast - Jadhav, Priyadarshini R.; Goyal, Sagar; Sheetal; Dhavalshankh, Gayatri; Dhavalshankh, Archana; Dhavalshankh, Ganesh (International Journal Of Community Medicine And Public Health, 2024)
Background: Psoriasis is a chronic inflammatory skin disease that requires long-term management, often necessitating systemic treatments for moderate to severe cases. Tofacitinib, a Janus kinase (JAK) inhibitor, and apremilast, a phosphodiesterase 4 (PDE4) inhibitor, are increasingly used in refractory cases. Monitoring liver function is crucial due to potential hepatotoxicity. This study compared the impact of tofacitinib and apremilast on liver function tests (LFTs) over 12 months in patients with refractory psoriasis. Methods: A retrospective cohort study was conducted at D. Y. Patil Hospital, Kolhapur, involving 150 patients treated between January 2019 and December 2021. Patients received either tofacitinib (5 mg twice daily) or apremilast (30 mg twice daily) for at least 12 months. Exclusion criteria included a history of liver disease, significant alcohol consumption, and incomplete medical records. Baseline and follow-up LFTs at 3, 6, and 12 months were analyzed using paired t-tests and independent t-tests. Results: Among 150 patients, 75 were treated with tofacitinib and 75 with apremilast. Baseline characteristics, including LFTs, were similar between groups. The tofacitinib group exhibited significant increases in ALT and AST levels at all follow-up points compared to the apremilast group (p<0.01). Mean ALT rose from 25.6 U/l to 42.3 U/l in the tofacitinib group, while in the apremilast group, it increased from 24.9 U/l to 28.9 U/l. ALP and bilirubin levels remained stable. Conclusions: Tofacitinib is associated with higher incidence of liver enzyme elevations than apremilast. Regular liver function monitoring is recommended for patients on tofacitinib.